Impact of Biotic Stresses on the Alpine Scrub, Pasture Land and Forest Area of Branwar Forest Division, Kashmir Himalaya (Global Journal of Science Frontier Research, 2012)
The present study was carried out for assessing different type of biotic stresses in Branwar Forests of Kashmir Himalaya. The Present Study area i.e., Branwar Forest Range lies over and above famous tourist area of Yus Marg on one side and Neel Nag Forest Lake on the other side. The present investigation was carries out from April, 2010 to April, 2011. The cumulative effect of the biotic interferences was significantly seen in the reduction of vegetation cover. The present study revealed that the prominent factor for the exploitation of the vegetation cover of Branwar forest study area at herbaceous level is simply the overgrazing. The increasing disturbances not only disturb the plant species diversity, richness and evenness significantly but various plant species have got completely eliminated by different kinds of interferences like overgrazing, deforestation, hydal power production, forest fire, Stone extraction, road construction etc. The forests in the region are suffering from severe biotic stress. The forests are intimately linked with the agro-ecosystems in the mountainous areas of the Himalaya and the depletion has definite and obvious impacts on the overall socioeconomic and agricultural scenario of the entire region.
Keywords: Forest; Importance Value Index; Grazing; Deforestation; Scrub; Biomass; Primary Productivity; Biotic Impact